Using the local wisdom of Wayang Kulit in implementing the project to strengthen the pancasila students profile (P5) in primary school - Rahayu, Kiswari Puji; Ngazizah, Nur; Suyoto, Suyoto (Journal of Research in Instructional, 2025)
The purpose of this study was to determine the implementation of the P5 theme of local wisdom of Wayang Kulit in class IV of a private primary school in Purworejo. Qualitative descriptive research was used. Data were collected through observation, interview, and documentation. Data sources included the principal, facilitator team, grade IV teachers, and student samples. Data were analyzed through data reduction, data presentation, and conclusion stages. The results showed that the P5 design of private primary schools in Purworejo includes three main stages: (1) Planning: The principal forms a team of facilitators, identifies school readiness, determines dimensions and themes, allocates time in weekly blocks, and develops project modules; (2) Implementation: Activities include an introduction, contextualization, real action in the form of making Wayang Kulit, and celebration of learning outcomes through class presentations; (3) Evaluation: Conducted through reporting results in the form of student project report cards and evaluating activities through reflection and two-way discussions between teachers and students. In the real action of P5, parents of students in private primary schools in Purworejo play an active role by providing resources in the form of tools and project materials, accompanying students at home, and actively participating in school meetings. It can be concluded that the implementation of P5 on the theme of local wisdom of Wayang Kulit in class IV of private primary schools in Purworejo is carried out systematically, integrates local wisdom, and involves the active participation of parents.